Bioidentidades e estratégias de comunicação: a deficiência intelectual como foco de experiência em uma sociedade centrada na negociação de conhecimentos - Almeida, Lia Raquel Lima (2015)
The research aims to examine the discourse on disability, in general, and intellectual disability, in particular, in contemporary Brazilian society and the relationships between communication, disability and biopolitics of social inclusion. As far as society is increasingly focused in the knowledge management, the research questions the intellectual disability as experience in our culture. Therefore, from a theoretical point of view, this research is based on the concepts of biopower and biopolitics in the writing of Michel Foucault and discussions of Nikolas Rose and Paul Rabinow about how the biotechnology has incited a new kind of relation with the body and the merge of one new approach to life. After this, discusses the relations between biopolitics and communication, from post-fordism transformations, in the researches of Negri and Lazzarato. From the methodological point of view, utilizes the experience notion brought by Foucault to identify on the statements of the Government (Viver Sem Limites), media (Veja e Folha de S. Paulo) and civil society (Movimento Down) the three points listed by the author as articulators of an experience: the description languages, strategies for intervention and modes of subjectification. The results showed that the discussion about intellectual disability are constructed around the notions of social inclusion and autonomy, with the exception of Veja magazine, that prioritizes healthcare approaches, such as advances in medicine and genetic risks. The research also realizes, that the speeches about the rights of people with disability rely on their biological bias, which leads to a reinforcement of the idea of bioidentity. In case of people with Down syndrome, this became even clearer when the genetically determined condition becomes structural identity factor. The politics of social inclusion have ensured rights access, without guaranty relationship and social acceptance. This paper also concludes that, despite of reaffirm the biological reference, the biosociability, by networks information and relationship on the internet, is important when try to seek to combine the possibilities of expanding the autonomist potential of this group with the creation of new feelings on them, bringing changes in how society see these people